Question

Solution to the equation y'' - y' - 6y = 0

107

likes536 views

Clarabelle

4.7

72 Answers

Certainly, let's focus on solving the differential equation y'' - y' - 6y = 0 step by step without much theory.
Step 1: Write down the differential equation:
y'' - y' - 6y = 0
Step 2: Find the characteristic equation by assuming a solution of the form y(t) = e^(mt):
m^2 - m - 6 = 0
Step 3: Solve the characteristic equation for m:
m = 3 or m = -2
Step 4: Write down the general solution:
y(t) = C1 * e^(3t) + C2 * e^(-2t)
Here, C1 and C2 are arbitrary constants that depend on initial or boundary conditions.

Frequently asked questions (FAQs)

What is 40% of 90?

+

What is the amplitude of the function y = 4sin(3x) in its standard form?

+

What is the value of f(x) when x = -2 for the reciprocal/rational function f(x) = 1/x?

+

New questions in Mathematics